Strategies Affecting Business Operations of Pet Product Retail in Bangkok: Strategies Affecting Business Operations of Pet Product Retail in Bangkok - Kummee , Kullasap; Roopsuwankun , Pattama; Ramwarungkura, Anuchai (RATANABUTH JOURNAL, 2026)
This research is a survey of pet product stores in Bangkok. The objectives are to 1) study the strategies of pet product stores in Bangkok and 2) study the relationship between strategies and business operations. The sample group consisted of 212 pet product store operators, calculated by Yamane. The research tool was a questionnaire. Data analysis using statistics is percentage, mean, standard deviation and multiple regression. using ready-made computer programs. The results of the study found that 1) Business-level strategies suitable for pet product stores in Bangkok consist of 3 strategies: the strategy to create difference has the highest average; Followed by the cost leadership strategy at the highest level and the strategy for penetrating specific market segments at a high level. 2) The relationship of business level strategies with business operations. It was found that all 3 business level strategies had a relationship with business operations with a statistical significance of .01.